The ultraviolet-to-mid-infrared spectral energy distribution of weak emission line quasars - Lane, R.; Shemmer, O.; Diamond-Stanic, A.; Fan, X.; Anderson, S.; Brandt, W.; Plotkin, Richard; Richards, G.; Schneider, D.; Strauss, M. (Institute of Physics Publishing, 2011)
We present Spitzer Space Telescope photometry of 18 Sloan Digital Sky Survey (SDSS) quasars at 2.7 = z = 5.9 which have weak or undetectable high-ionization emission lines in their rest-frame ultraviolet (UV) spectra (hereafter weak-lined quasars, or WLQs). The Spitzer data are combined with SDSS spectra and ground-based, near-infrared (IR) photometry of these sources to produce a large inventory of spectral energy distributions (SEDs) of WLQs across the rest-frame 0.1-5 µm spectral band. The SEDs of our sources are inconsistent with those of BL Lacertae objects which are dominated by synchrotron emission due to a jetaligned close to our line of sight, but are consistent with the SED of ordinary quasars with similar luminosities and redshifts that exhibit a near-to-mid-IR "bump," characteristic of hot dust emission. This indicates that broad emission lines in WLQs are intrinsically weak, rather than suffering continuum dilution from a jet, and that such sources cannot be selected efficiently from traditional photometric surveys.